Trophic Relationships and Food Supply of Heterotrophic Animals in the Pelagic Ecosystem of the Black Sea - (:unkn) unknown (Istanbul, Turkey, 2009)
During recent decades, the Black Sea has been affected by many negative factors that strongly changed the condition of its ecosystem. Especially trophic relationships in the Black Sea pelagic system became very vulnerable influencing the food supply, productivity and abundance of many species and populations of this marine basin. Food is one of most important link between biota and its environment. In this monograph, the role and variability of trophodynamic processes that effect the well-being (health) of main heterotrophic components of ecosystem were analysed in detail for a few key species as indicators for estimation of ecosystem condition in whole. These are most significant mass species of the Black Sea pelagic ecosystem. Among copepods this is Calanus euxinus that dominates the mesozooplankton which makes up the fodder base of planktivorous fishes. Among gelatinous these are medusa Aurelia aurita and the alien ctenophores Mnemiopsis leidyi and Beroe ovata which affected strongly mesozooplankton composition. Lastly among fishes the anchovy Engraulis encrasicolus ponticus and sprat Sprattus sprattus phalericus that dominate small pelagic fishery. We considered in this monograph: • Diel feeding behaviour, in situ feeding rate of Calanus euxinus and impact of mesozooplankton on primary production and phytoplankton biomass. • The effect of vertical migrations on energy budget and its components in C. euxinus; metabolic substrates used in catabolic processes under both aerobic and hypoxic conditions, the role of reserve lipids and effect of abiotic factors on individual growth and population structure of this species. • The intensity and efficiency of ingestion and energy transformation in three gelatinous species ( jellyfish Aurelia aurita, ctenophores Mnemiopsis leidyi and Beroe ovata) and their predatory impact on zooplankton community. • Nutritional condition and food supply of anchovy and sprat in the close interaction with natural biotic and abiotic and anthropogenic factors. • Tendencies in this interaction during long time space: since 1960 s till present years. • Estimation of population condition of these species and its long-term change. This monograph is the collective work of Ukrainian and Turkish scientists studying complex hydrobiological problems of the Black Sea. Its aim is to reveal the significance of nutritional factors on the ecology of Black Sea biota, including changes which have already occurred, as well as offering some insight into changes that may happen in the future. Our joint investigations started in the first half of the 1990s, when conditions for the close cooperation of researchers from the two countries were suitable after the collapse of the Soviet era. This spirit continues to the present day. Professor Ümit Unluata, Director of Erdemli Institute of Marine Sciences (Middle East Technical University, Ankara) was of paramount importance in organising and fostering the work undertaken. We would like to devote this monograph to the memory of him, who died so prematurely. We are also grateful to Academician Professor V. N. Eremeev, Director of the Sevastopol Institute of Biology of the Southern Sea (National Academy of Sciences of Ukraine), and to the directors of Erdemli Institute of Marine Sciences (Professor Ilkay Salihoglu, Professor Sukru Besiktepe and Professor Ferit Bingel) who also made significant contributions to the Ukrainian–Turkish collaboration. We are grateful to Dr Bill Parr from the Black Sea Ecosystem Recovery Project for his valuable efforts in improving earlier drafts. All these investigations were carried out within the framework of the following five NATO linkage-grants: • Pelagic animal food supply in the unstable Black Sea environment, • Will the new alien ctenophore Beroe ovata control the plankton community in the Black Sea? • Grazing, growth and production of Calanus euxinus in the Black Sea, • Bioindicators for assessment of Black Sea ecosystem recovery, • Adaptability and vulnerability of marine species in changing environments. And four TUBITAK - NASU joint projects: • Quantification of the recent ctenophore invader Beroe ovata impact in the Black Sea • Monitoring of the Black Sea anchovy and sprat, • Salinity tolerance as a key factor of invasion success of the copepods of Calanus genus into the Sea of Marmara, • Salinity tolerance as a key factor of invasion success of the mesozooplankton species into the Sea of Marmara. We hope that this publication will make a substantial contribution to future studies of the Black Sea ecosystem and offers further understanding of those features regulating biological processes in this unique marine basin.